QD/SnO2 Photoactivated Chemoresistive Sensor for Selective Detection of Primary Alcohols at Room Temperature - Maria Yu. Skrypnik; Vadim B. Platonov; Daria A. Kurtina; Oleg G. Sinyashin; Marina N. Rumyantseva; Roman B. Vasiliev (Chemosensors)
Sensors based on nanocomposites of quantum dots (QDs) and wide-gap metal oxides are of exceptional interest for photoactivated detection of toxic and pollutant gases without thermal heating. However, the class of detecting gases has been limited almost exclusively to oxidizing gases like NO2. Here, we designed a photoactivated sensor for the selective detection of primary alcohols at room temperature using CdSe quantum dots coupled to a wide-gap SnO2 semiconductor matrix. Our concept of the sensor operations is based on the photochemical reaction of primary alcohols via photoactivated QD-SnO2 charge transfer and does not involve chemisorbed oxygen, which is traditional for the operation of metal oxide sensors. We demonstrated an efficient sensor response to C1–C4 primary alcohols of ppm concentration under photoexcitation with a yellow LED in the absence of a signal from other volatile organic compounds (VOCs). We believe that proposed sensor concept opens up new ways to design photoactivated sensors without heating for the detection of VOCs.